Testing of solar thermal collectors under transient conditions - Osório, Tiago (2015)
The most important standard for collector testing in Europe is the EN 12975:2006 which is applied in all the major laboratories and is the reference for the Solar Keymark certification. Besides the steady-state method, the EN 12975 allows the application of the quasidynamic method performed outdoors in natural conditions with variable radiation and ambient temperature. The available number of days for each test was investigated by analyzing meteorological data series acquired in the Solar Energy Laboratory (LES) in Lisbon since 2008 showing the advantage of the quasi-dynamic test. Both the steady-state and the quasi-dynamic methods were applied to five collectors of different types (two flat plate collectors, one evacuated tube collector with a back reflector and direct flow circulation, one evacuated tube collector with heat pipes, and a CPC collector). The results were compared and a good agreement between the steadystate and the quasi-dynamic test results was observed. Issues concerning the incidence angle modifiers and the effective thermal capacity of the collectors were analyzed in detail, which resulted in the identification of model and test limitations. Suggestions are given to improve the test methodology and the data analysis of quasi-dynamic test